Metode Analisis Wacana Teun Van Djik Dalam Penelitian Ilmu Perpustakaan Dan Informasi - Riza, Muhamad (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The adoption of information technology into library and information studies has shifted the research of this area into more of quantitative and statistic-driven as well as IT based research. Not that those researches are unnecesarry, but the adoption of Information Technology has diminished the role of library in the cultural context, especially in its research topics. Humanities-based approach on Library and Information Science researches have reduced dramatically in its quantity for decades considering that earlier researches of Library and Information area its in humanities. This research focuses on applying Discourse Analysis especially that of Teun Van Djik’s into Library and information science research. The paper uses qualitative method using descriptive approach. This paper finds that there are saveral topics that can be investigated and analysed by DA namely: 1) Analysing library-based policies (eg. Colection development policy). 2 Analysing certain library policies on library users, and lasty 3) analysing news on library or/and library information studies on mass media.